A Study on Pradhan Mantri Kisan Samman Nidhi (Pm-Kisan) With Reference to the North Eastern States, India - Prantik Bordoloi Prantik Bordoloi; Nilutpal Dutta; Maikel Swargiary; Nilakshi Kalita (Journal of Social Science, 2023)
The PM-KISAN is a central sector scheme under the Govt. of India which aims to provide income supports to farmers to facilitate timely access to agricultural inputs. The cash benefits under this scheme under enhance the financial capacity of the beneficiaries to invest in the agriculture and in the acquisition of modern techniques in agriculture. The families and households who are highly dependent on agriculture and have poor access to credits get more benefits from the scheme. In this study we explore, how far the scheme has spread across the states. This work provides a comprehensive overview of the implementation of the PM-KISAN scheme in the eight states of north-east India. The study will also shed light on the comparative study on the number of people availing the benefits of this scheme in different states. Moreover a gender wise analysis is also made in this direction. Through this publication, we also aim to create awareness about the PM-KISAN scheme among the farmers of north-east India. It is evident from the study that farmers of Assam have benefited more from the scheme as compared to other north eastern states. The percentage of male beneficiaries from the scheme is highest in Meghalaya with 96 % and the state with the lowest percentage of male beneficiaries from the scheme is Manipur with 45.8%.